The Role of Human Resource Management in Enhancing Company Performance and Productivity - Dipoatmodjo, Tenri Sayu Puspitaningsih (Malaqbi Publisher, 2024)
HR management has a very important role in the continuity of the company. This problem is due to matters related to performance, motivation, job satisfaction, and productivity if the will is not fulfilled, it will lead to the company’s sustainability being disrupted. Human resource management is the process of dealing with various problems within the scope of employees, clerks, laborers, managers and other workers to be able to support the activities of an organization or company in order to achieve predetermined goals. Therefore managers must ensure that the company or organization has the right workforce in the right place, and at the right time, who has the ability to complete tasks that will help the company achieve its overall goals effectively and efficiently. The writing method uses the literature review method (libari research). Human Resource Management (HR) is a method of human resource management in an organization to achieve the maximum goals of the organization through the development of the human resources themselves. Human Resource Management is drip management focusing on the human factor of production with all activities to achieve company goals. Human resources are investment holding an important role for the company. Without human resources, other production factors cannot be maximized to achieve company goals. The role of humans in achieving this goal is very important in achieving organizational goals. So in simple terms actually human resource management is managing human resources. Of all the resources available in the organization, human resources are very important and very decisive. All the potential possessed by human resources greatly influences the organization’s efforts to achieve its goals.